G516 Improving paediatric prescribing practice in a district general hospital through implementation of a quality improvement project. (27th April 2015) - Donnelly, P; Lawson, S; Watterson, C; Ledwidge, M
Abstract : Context: This quality improvement project was carried out in the paediatric ward of a district general hospital in Northern Ireland. This work was carried out as part of a cross-border patient safety collaborative organised by the Co-operation and Working Together Group (CAWT). Problem: Prescribing errors are a recognised cause of adverse incidents having a direct effect on patients. They impact on the doctor-family relationship and result in breakdown of trust. The existing incident reporting system underestimates medication prescribing errors. Assessment of problem and analysis of its causes: A retrospective analysis of prescribing errors between January and December 2013 identified two errors, felt to be secondary to underreporting. Subsequently a baseline audit was performed reviewing patient demographics, allergy status, generic prescribing, drug dosage, timings, drug reconciliation, antibiotic prescribing (indication and duration) and legibility. Twelve drug charts were analysed highlighting 32 errors. A driver diagram identified three components contributing to prescribing errors and relevant tests of change were developed. The three primary drivers included; education and communication, practical prescribing changes and medicine reconciliation. Intervention: Seven tests of change were implemented comprising of: presentation of baseline data, staff completion of an online learning module, introduction of a safety notice board, inclusion of data to the nursing safety brief, introducing a medication administration checklist, ensuring staff access to a regional patient information system, appointment of a ward pharmacist and finally developing a pocket-sized antibiotic reference tool. Study design: This was a quality improvement project performed using plan-do-study-act (PDSA) cycles and multiple audit cycles. Strategy for change: Each intervention was implemented sequentially over a 6 month period and effectiveness assessed by ongoing audit. Ten drug charts were selected at random by the staff nurse allocated to medications on the day of audit. Results were collated in a run diagram in order to disseminate progress to the team. Measurement of improvement: The charts were audited using a predesigned proforma and the total number of errors counted. These were subcategorised and results displayed in graphical format after each intervention. In total seven audit cycles were completed. The number of errors including percentage change following each intervention is as follows: Intervention 1; 32 (+19%), Intervention 2; 31 (+15%), Intervention 3; 17 (-37%), Intervention 4; 12 (-56%), Intervention 5; 15 (-44%), Intervention 6; 7 (-74%), Intervention 7; 10 (-63%). Effects of changes: The changes led to a global improvement in paediatric prescribing- a reduction in errors of 63%. This represents a significant improvement in prescribing practice thereby reducing the potential impact on patients of prescribing errors. The main difficulty encountered during the PDSA cycles was regarding resistance to change and buy-in from junior medical staff. Continued encouragement helped to address these issues. Lessons learnt: There were two unsuccessful PDSA cycles; presentation of baseline data and completion of an online learning module. This quality improvement project was performed in the six months prior to changeover of staff. It would have been a beneficial project during the initial six month period in order to improve sustainability and patient safety within the trust. Message for others: We need to introduce permanent and successful measures to reduce prescribing errors in order to minimise the impact of staff changeover and knowledge deficits. The most significant change followed the introduction of a patient safety notice board which reduced the number of errors from 31 to 17. This represents a percentage reduction of 45% following a single intervention. It follows from this that education and awareness is paramount to continued professional development and quality improvement.